A case of adult congenital laryngeal cleft asymptomatic until hypopharynx cancer treatment. Issue 3 (June 2018) - Shimizu, Kotaro; Uno, Atsuhiko; Takemura, Kazuya; Ashida, Naoki; Oya, Ryohei; Kitamura, Takahiro; Takenaka, Yukinori; Yamamoto, Yoshifumi
Abstract: Laryngeal cleft is an anomaly of failed posterior closure of the larynx. Most cases are diagnosed and need treatment early in life due to respiratory and swallowing problems. We report an unusual case of a 66-year-old man with an asymptomatic laryngeal cleft until treatment for hypopharyngeal cancer. During concurrent chemoradiotherapy (CCRT), despite reduced tumor volume, he presented severe dysphagia and dyspnea, followed by severe pneumonia twice. Because CCRT had to be discontinued, a pharyngolaryngectomy was performed for the cancer treatment. The resected specimen showed total removal of the tumor and a total longitudinal cleft of the cricoid cartilage, classified as a type III laryngeal cleft by the Benjamin and Inglis' classification. A review of computed tomography images indicated that the redundant mucosa from bilateral edges closed the separation of the posterior cricoid cartilage and narrowed the laryngeal airway during CCRT. Adult presentations of laryngeal cleft are quite rare with only ten reported cases in English literature; the present case is of the oldest patient. Undiagnosed cases with laryngeal cleft may exist asymptomatically or without severe symptoms. The awareness of this condition may increase its diagnosis as a cause of diseases such as aspiration and recurrent pneumonia even in adult patients.